KAJIAN ATAS PERBANDINGAN PENYUSUTAN AKTIVA TETAP MENURUT AKUNTANSI (KOMERSIAL) DAN MENURUT KETENTUAN PERATURAN PERUNDANG – UNDANGAN - SUPARMAN SUPARMAN (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTThe existence of different concepts, measurements, methods, and the recognition of income and expensesbetween accounting and taxation lead to differences between accounting income to taxable income. Onecomponent of the burden of confession differ between accounting and taxation is the depreciation of fixed assets.The difference lies at the commencement of depreciation, depreciation basis, grouping, useful life anddepreciation method selected. Any fixed assets owned and used by every company, depreciation must be done,both for accounting purposes and for tax purposes. One goal of this study was to determine whether thedepreciation of fixed assets made by the Company in general are in accordance with GAAP for accountingpurposes and provisions of laws - taxation law for tax purposes.The research method used is descriptive analytical method. Based on research results, depreciation offixed assets made by the Company in general not fully in accordance with GAAP for accounting purposes andprovisions of laws - the tax law for tax purposes.In general, for accounting purposes (commercial), there is stilla mistake in terms of determining the commencement of depreciation, which the company calculates depreciationstarts in the acquisition of fixed assets, which should begin at the time the asset is put into use or begun to beexploited by the company. For tax purposes (fiscal), the grouping of fixed assets and the benefits aretreated the same as the accounting provisions, which should follow the provisions of laws - taxation law, namelyArticle 11 paragraph (6) Income Tax Act and the Regulation of the Minister of Finance No.96/PMK /PMK.03 / 2009.To that end, the company in order to be more rigorous and careful in classifying fixed assets to the list offixed assets, both for accounting purposes and for tax purposes. So also in the depreciation of fixed assetsnecessary understanding and accuracy in applying the provisions of accounting (GAAP) and provisions of l aws taxationlaw, as this will affect the amount of depreciation expense, which will then beinfluential also in thedetermination of accounting income and taxable income.Keywords: Depreciation of Assets, Tax Law, Capital Lease